GREENING AND TREE PLANTING TO REALIZE ASRI SCHOOL - Adriansyah, Endi; Marhadi, Marhadi; Viareco, Hariestya; Herawati, Peppy; Sufra, Rifqi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
Tree planting has the aim of reforestation and greening for conservation, greening is an effort to create a beautiful and useful area and greening is increasing the area of ​​RTH (Green Open Space). This community service is at SD N 2 Senawar. Community service aims to increase tree planting in schools and foster students' character to love the environment. Community service methods are presentation, discussion and practice methods. Transfer of knowledge and technology given to residents of SD N 2 Senawar school. community service activities participants can find out about tree planting and reforestation activities properly and can reduce the impact of environmental pollution.